Is spontaneous onset of labour more successful than induced labour among patient with one previous scar? A retrospective study in Ampang Hospital, Malaysia - Khalid, S; Masri, M; Shamsir M.; Ganesalingam, M (Wiley-Blackwell, 2024)
Indexed by WOS